2001
DOI: 10.2113/gseegeosci.7.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Long-term water quality trends at a sealed, partially flooded underground mine

Abstract: An abandoned underground coal mine complex in southeastern Ohio was hydraulically sealed in 1980 by a 300-m long subsurface clay dike and mine-entry seals near the down-dip coal outcrop. Clay plugs also were emplaced in separate entries at a higher elevation than the dike. The intent was to flood the mine to decrease acid mine drainage. A few months after construction, an entry-seal clay plug blew out at an elevation corresponding to 85-90 percent inundation, and drains in natural materials supporting the dike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Previous studies (López and Stoertz 2001;Stoertz et al 2001) of the abandoned mines in the region have shown seasonal variations with respect to discharge, with the highest discharge usually occurring in the spring months and the lowest occurring during summer when evapotranspiration is highest. The Corning discharge has variable flow, from \28 L s -1 to [140 L s -1 (\1 to [5 cfs), and high acidity and iron loads, averaging 593 kg day -1 acidity and 257 kg day -1 iron (McCament 2004).…”
Section: Site Descriptionmentioning
confidence: 95%
“…Previous studies (López and Stoertz 2001;Stoertz et al 2001) of the abandoned mines in the region have shown seasonal variations with respect to discharge, with the highest discharge usually occurring in the spring months and the lowest occurring during summer when evapotranspiration is highest. The Corning discharge has variable flow, from \28 L s -1 to [140 L s -1 (\1 to [5 cfs), and high acidity and iron loads, averaging 593 kg day -1 acidity and 257 kg day -1 iron (McCament 2004).…”
Section: Site Descriptionmentioning
confidence: 95%
“…However, considerable transience is typically observed in the quality of these outflows, with the concentrations of pollutants being highest in the period immediately following initial onset of outflow, with a gradual improvement over time until an asymptotic level of pollution is established (Younger 1997;Wood et al 1999;Gzyl and Banks 2007). Unfortunately, this asymptotic level all too often still exceeds the assimilatory capacity of the receiving water body, so that long-term treatment of the polluted water is required (Younger 1997;Stoertz et al 2001). Predicting the locations, flow rates and quality of mine water outflows is therefore highly desirable if uncontrolled pollution is to be avoided.…”
Section: Why Predict Post-closure Hydrogeology Of Coalfields?mentioning
confidence: 99%
“…Today, after observations of recent coal mine closures, postclosure mine water management has become a critical element in mine permitting and design. Realistic prediction of the duration and timing of postclosure mine flooding and the locations of potential future surface discharge(s) are considered critical information for mine design and planning [7,9,10]. However, such predictions are hampered by uncertainties related to the same factors that have caused flooding to proceed differently within different mines.…”
Section: Introductionmentioning
confidence: 99%